The efficacy and safety of torasemid in the treatment of arterial hypertension in different clinical situations - O D Ostroumova (Системные гипертензии, 2017)
The article considers issues of efficiency and safety of the use of torasemid, a loop diuretic, with the additional property of antagonist of the mineralocorticoid receptor in the treatment of arterial hypertension in different groups of patients.